NATIONAL SECURITY IN THE CONTEXT OF EURO-ATLANTIC INTEGRATION OF UKRAINE: A PHILOSOPHICAL REFLECTION - Данильян, Олег Геннадійович; Дзьобань, Олександр Петрович (Вісник НЮУ імені Ярослава Мудрого: Серія: Філософія, філософія права, політологія, соціологія, 2020)
The Problem setting. General globalization processes on the European continent and the aggressive actions of individual States caused a radical revision of the system of ensuring national security of Ukraine, which transformed in the direction of Euro-Atlantic integration. Dramatic geopolitical changes of the last decade, the military-political confrontation with the Russian Federation radically transformed the whole organization of international relations established after the Second world war. Therefore, the problem of ensuring national security is our country in modern conditions a special, unprecedented, value. Recent research and publications analysis. The availability of scientific publications allows us to conclude that the research of the designated problems is carried out mainly within the framework of political and economic science. Attempts holistic philosophical understanding of the nature and determinants of the direction of development of Ukrainian society in the Euro-Atlantic area are insufficient. Paper objective. The purpose of this article is to attempt a philosophical understanding of the need for Euro-Atlantic integration of Ukraine in the context of ensuring its national security. Paper main body. Ukraine is becoming a more active player in international relations due to its geopolitical position. Modern Ukraine plays an extremely important role in the development of political and economic cooperation on the European continent and in adjacent areas, providing in conditions of extreme military and information aggressive activity of Russia regional stability and security. For Ukraine, the issue of Euro-Atlantic choice is not rhetorical. History cites many vivid examples that clearly demonstrate that their historical-cultural and mental sources Ukraine has always belonged to the transatlantic space. In the foreign policy priorities of our state, this selection occupies a special place. The modern foreign political course of Ukraine for Euro-Atlantic integration implies the desire to become part of the most efficient and effective collective security system, with clear guarantees of their own security. The intensification of European integration processes means more intensive inclusion of Ukraine in international cooperation for conflict and counter the latest threats in the security sphere. The main directions of ensuring national security in the sphere of international cooperation is integration into the international system of security and cooperation on prevention of illegal actions in the sphere of security. The article highlights how obvious the prospects and benefits of Euro-Atlantic integration of Ukraine and its possible risks and threats to national security. Conclusions of the research. Despite the fact that a full-fledged member of the Euro-Atlantic space in the short and even medium term, Ukraine will not be able to become, it can significantly increase cooperation with the countries of the West, which will greatly enhance her chances and accelerate the pace of integration. The course of Euro-Atlantic integration is not limited to declarations and statements. This is a concrete, planned, multi-faceted activity. Being interconnected and interdependent, the problems of security and development of modern society require a comprehensive study because of their joint decisions determine the future as a separate country and humanity in General.